Analisis Pengaruh Suku Bunga BI, Jumlah Uang Beredar, Tingkat Kurs Dan Produk Domestik Bruto (Pdb) Terhadap Tingkat Inflasi Di Indonesia Tahun 2015.3-2023.3 - Figo Loindong; Ita Pingkan F. Rorong; Mauna Th. B. Maramis (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
Monetary policy is the action taken by the central bank to regulate the amount of money in the economy in order to achieve economic growth goals, including price stability, economic improvement, and adequate job creation. The importance of the inflation factor for Indonesia is undeniable because it has a major impact on the country's economic condition. By understanding the nature and triggers of inflation, researchers can provide valuable insights for monetary authorities to control the rate of inflation. The aim of this research is to determine the influence of BI interest rates, money supply, exchange rate and gross domestic product (GDP) on the inflation rate in Indonesia 2015.3-2023.3 Data analysis method is the ECM test, F test analysis shows a significant regression model, with variables such as the BI Interest Rate, Money Supply, and the Rp/USD Exchange rate significantly influence inflation. The high R-squared value and the absence of autocorrelation problems strengthen the validity of the model.